Intestinal HIF-2α Regulates GLP-1 Secretion via Lipid Sensing in L-CellsSummary - Raja Gopal Reddy Mooli; Dhanunjay Mukhi; Anil K. Pasupulati; Simon S. Evers; Ian J. Sipula; Michael Jurczak; Randy J. Seeley; Yatrik M. Shah; Sadeesh K. Ramakrishnan (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Background & Aims: Compelling evidence shows that glucagon-like peptide-1 (GLP-1) has a profound effect in restoring normoglycemia in type 2 diabetic patients by increasing pancreatic insulin secretion. Although L-cells are the primary source of circulating GLP-1, the current therapies do not target L-cells to increase GLP-1 levels. Our study aimed to determine the molecular underpinnings of GLP-1 secretion as an impetus to identify new interventions to target endogenous L-cells. Methods: We used genetic mouse models of intestine-specific overexpression of hypoxia-inducible factor (HIF)-1α and HIF-2α (VhlΔIE), conditional overexpression of intestinal HIF-2α (Hif-2αLSL;Vilin-Cre/ERT2), and intestine-specific HIF-2α knockout mice (Hif-2αΔIE) to show that HIF signaling, especially HIF-2α, regulates GLP-1 secretion. Results: Our data show that intestinal HIF signaling improved glucose homeostasis in a GLP-1–dependent manner. Intestinal HIF potentiated GLP-1 secretion via the lipid sensor G-protein–coupled receptor (GPR)40 enriched in L-cells. We show that HIF-2α regulates GPR40 in L-cells and potentiates fatty acid–induced GLP-1 secretion via extracellular regulated kinase (ERK). Using a genetic model of intestine-specific overexpression of HIF-2α, we show that HIF-2α is sufficient to increase GLP-1 levels and attenuate diet-induced metabolic perturbations such as visceral adiposity, glucose intolerance, and hepatic steatosis. Lastly, we show that intestinal HIF-2α signaling acts as a priming mechanism crucial for postprandial lipid-mediated GLP-1 secretion. Thus, disruption of intestinal HIF-2α decreases GLP-1 secretion. Conclusions: In summary, we show that intestinal HIF signaling, particularly HIF-2α, regulates the lipid sensor GPR40, which is crucial for the lipid-mediated GLP-1 secretion, and suggest that HIF-2α is a potential target to induce endogenous GLP-1 secretion.